2017
DOI: 10.1097/qco.0000000000000405
|View full text |Cite
|
Sign up to set email alerts
|

What, where and why: exploring fluorodeoxyglucose-PET's ability to localise and differentiate infection from cancer

Abstract: Patients with cancer are vulnerable to infection and fever, and the causes of these are frequently unclear using conventional diagnostic methods leading to high morbidity and mortality, length of stay and costs of care. FDG-PET/CT, with its unique complementary functional and anatomical information as well as its whole-body imaging capability, has demonstrated use in detecting occult infection in immunocompromised patients, including invasive fungal and occult bacterial infections, as well as defining extent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 179 publications
0
14
0
Order By: Relevance
“…The role of diagnostic imaging, specifically fluorodeoxyglucose positron emission tomography (FDG-PET) combined with computed tomography (CT) or magnetic resonance imaging (MRI), for investigation of prolonged FN is also emerging as a potentially useful tool. 28,29 A retrospective study of children with cancer and prolonged or recurrent FN found that, compared to conventional imaging, FDG-PET/CT identified additional sites of clinically significant infection/inflammation compared to conventional imaging. The study also showed that the FDG-PET results had a clinical impact in 80%, leading to de-escalation or stopping of antibiotics in many patients.…”
Section: Diagnosis and Initial Investigation Of Fnmentioning
confidence: 99%
“…The role of diagnostic imaging, specifically fluorodeoxyglucose positron emission tomography (FDG-PET) combined with computed tomography (CT) or magnetic resonance imaging (MRI), for investigation of prolonged FN is also emerging as a potentially useful tool. 28,29 A retrospective study of children with cancer and prolonged or recurrent FN found that, compared to conventional imaging, FDG-PET/CT identified additional sites of clinically significant infection/inflammation compared to conventional imaging. The study also showed that the FDG-PET results had a clinical impact in 80%, leading to de-escalation or stopping of antibiotics in many patients.…”
Section: Diagnosis and Initial Investigation Of Fnmentioning
confidence: 99%
“…18 F-FDG PET-CT has already been reported to detect infiltrates caused by PJP earlier than the standard chest radiograph. 13 In addition, in our study, 18 The concept of "staging" IFI, along the same line as we do with tumours, is beginning to take root. 15 IFI presentation can be very heterogeneous, and multiple organ involvement is not uncommon.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have evaluated 18 F-FDG PET-CT in invasive candidiasis, finding that 18 F-FDG PET-CT is more sensitive than CT or ultrasound for detection of dissemination of Candida, particularly of hepatosplenic involvement, 13,16,17 but few have investigated its role in fungal endocarditis. In the case of fungemia, staging should include the evaluation for endocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations